2008
DOI: 10.1017/s1368980008002838
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal obesity on initiation and duration of breast-feeding in Greece: the GENESIS study

Abstract: Objective: The current paper aims to describe the characteristics of mothers failing to initiate breast-feeding, provide information on the factors contributing to longer duration of breast-feeding and identify the association of maternal obesity with both initiation and duration of breast-feeding in the Greek population. Design: Data from the cross-sectional GENESIS (Growth, Exercise and Nutrition Epidemiological Study In preSchoolers) study were used. Mothers were categorized by their pre-pregnancy BMI and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
38
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 53 publications
11
38
0
7
Order By: Relevance
“…11,15,16,[18][19][20][21][22][23] Of the 13 studies that evaluated BF duration, 10 found an association between maternal obesity or overweight and reduced duration of BF [17][18][19][20][21][23][24][25] (Table 1). For some of the studies, the results were heterogeneous (present for BF initiation but not duration, or vice versa), or the association was present only for specific population groups and not others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,15,16,[18][19][20][21][22][23] Of the 13 studies that evaluated BF duration, 10 found an association between maternal obesity or overweight and reduced duration of BF [17][18][19][20][21][23][24][25] (Table 1). For some of the studies, the results were heterogeneous (present for BF initiation but not duration, or vice versa), or the association was present only for specific population groups and not others.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies analyzed the possible interaction between gestational weight gain and maternal prepregnancy BMI. Manios et al 22 evaluated gestational weight gain separately from prepregnancy BMI, finding that the two variables were highly correlated in regression analyses. The study by Baker et al 25 found that gestational weight gain did not interact with or confound the relationship between prepregnancy BMI and terminating BF, although gestational weight gain increased the odds of termination of BF inconsistently when prepregnancy BMI was not in the model.…”
Section: Medical Complications Including Gestational and Preexistingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Manios et al studied 2375 preschool children, aged 1-5 years, in Greece. In their study, high maternal prepregnancy BMI had a negative association with the initiation of breastfeeding, but not maternal gestational weight gain (16). tional weight gain above the IOM recommendations were at risk of early discontinuation of exclusive breastfeeding (15).…”
Section: Discussionmentioning
confidence: 80%
“…In a study by Manios, 37.1% and 31.1% of Greece women (n, 2374) had inadequate and excessive gestational weight gain, respectively (16). Moreover, in a study conducted in Guilan, North of Iran, the percentage of urban women who gained weight above the IOM recommendation was 10%, while 41.1% gained weight less than the recommended range (17).…”
Section: Discussionmentioning
confidence: 98%